Dimensi Ekonomi Islam dalam Sistem Pembiayaan Bank Syariah - Aan Suhendri; Ahmad Muklishin (Universitas Islam Negeri Alauddin Makassar, 2018)
Financing or financing is a funding provided by a party to other parties to support planned investments, either alone or institution. In other words, financing is funding issued to support planned investments. The term in financing is basically born of the notion I believe, I trust, that I believe or I trust. The word financing means trust (trust) which means bank trust to someone to carry out the trust given by the bank as shahibul mal The fund must be used correctly, fair, and must be accompanied by clear and mutually beneficial ties and conditions for both sides.